PENENTUAN PREMI TAHUNAN POLIS PARTISIPASI ASURANSI JIWA ENDOWMENT DENGAN OPSI SURRENDER - EKAWATI, DARMA ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Premium paid by policyholders should be invested by insurance company to maintain the company. Related to the invested premiums, insurance company offers a contract to policyholders called life insurance participating policy. In this contract, at the end of each policy year, the insurance company grants a bonus, which is credited to the mathematical reserves and depends on the performance of reference portfolio. However, to make it more interesting, the insurance company can put additional feature in the contract which allows policyholders to giveup the contract. This contract is called life insurance participating policies with surrender option. The pricing of life insurance participating policies with surrender option is affected by the value of reference portfolio. In this research, we assume the rate of return of the reference portfolio would follow a regime switching lognormal model. This thesis describes about determination of bonus rate under regime switching model, and the annual premiums of endowment life insurance participating policies with surrender option. Keywords: Life Insurance, Participating Policy, Surrender Option, Regime Switching Lognormal Model, EM Algorithm